Research about Physical Activity and Sport Science in Spanish University from 1981 to 1996 - M.A. Delgado; J. Medina (Asociación Española de Ciencias del Deporte, 2010)
This study tries to analyze the researchs accomplished in the spanish university since 1981 to 1996. Previous we studied the existent taxonomies about the áreas of Physical Activity and Sport Sciences. It stands out the complexity and need to realize a consensied taxonomy to study the researching lines of área. On inductive way we proceeded to categorize the topics of investigation of each doctoral thesis. At last it finished with a analysis about the evolution of researchs by years (academic course), universities, áreas and subjects. KEY WORDS: Research, Physical Activity and Sport, Taxonomy